A CRITIQUE OF THE TENTATIVE STATEMENT OF ACCOUNTING PRINCIPLES. - Stempf, Victor H. (The Accounting Review, 1938)
The article presents a critique of the tentative statements of accounting principles. Characteristics of separate industries, and of units of the same industry differ; and these differences require diverse application of recognized accounting principles to the solution of analogous but nevertheless dissimilar problems. This experimental formulation of principles leaves its mark upon the development of accounting. The ultimate product will come into the hands not alone of the profession but also into those of the banker, business man, investor, and regulatory authorities. The ideal must contemplate clear simple statements which leave no room for ambiguity, in order that there may be a concise meeting of the minds. The author holds that rules should be stated simply as acceptable applications of recognized principles and not as mandatory procedures. This is the philosophy which underlies the standards of Public Accounting practice already established, in respect of audit procedure, which recognize that in a variety of instances other procedures may be substituted and that circumstances may justify the omission of procedures recommended.